Regional fat mobilization and training type on sedentary, premenopausal overweight and obese women. (17th September 2013) - Carnero, Elvis A.; Amati, Francesca; Pinto, Ronei S.; Valamatos, Maria José; Mil‐Homens, Pedro; Sardinha, Luis B.
<x xml:space="preserve">Abstract</x> Objective Little is known about the influence of different training types on relative fat mobilization with exercise. The purpose of this study was to analyze the changes induced by aerobic training (AT), resistance (RT) or a combination of both (AT+RT) on total fat mass (TFM) and regional fat mass (RFM). Further, the relative contribution of different regions, upper limbs (UL), lower limbs (LL), and trunk (Tr), were compared. Design and Methods Forty‐five overweight and premenopausal women were randomized in either AT, RT or AT+RT. All training groups exercised for the same duration (60 min), 3 times per week for 5 months. Body composition was estimated using dual energy X‐ray absorptiometry. Results TFM decreased significantly in all groups (−4.6 ± 1.9 kg; −3.8 ± 2.6 kg, and −4.7 ± 3.0 kg in AT, RT, and AT+RT groups respectively; P < 0.001). The relative contribution of FM into each segment changed significantly: TrFM represented 46.6% ± 5.8% of TFM at baseline and reduced to 43.1% ± 5.5% (P < 0.001); LLFM was 39.7% ± 5.8% vs. 41.6% ± 5.7% (P < 0.01); ULFM was 11.3% ± 1.3% vs. 12.2% ± 1.4% (P < 0.01). Conclusion Training type did not influence changes of TFM and RFM. Fat mobilization came predominantly from Tr in all training protocols. These findings suggest that overweight and obese women can reduce TFM and RFM, independently of training type.